2014
DOI: 10.1002/polb.23523
|View full text |Cite
|
Sign up to set email alerts
|

Tailored side‐chain architecture of benzil voltage stabilizers for enhanced dielectric strength of cross‐linked polyethylene

Abstract: The synthesis and physico‐chemical properties of seven benzil‐type voltage stabilizers are reported. The benzil core is substituted with alkyl chains of different length that are linked to the benzil core via an ester, ether, or tertiary amine group. All additives can be melt‐processed with low‐density polyethylene (LDPE). Fourier‐transform infrared spectroscopy confirms that benzil compounds are not affected by the LDPE cross‐linking reaction induced by dicumyl peroxide. Moreover, a combination of gel content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 22 publications
1
59
0
Order By: Relevance
“…[1][2][3][4][5][6][7] These additives scavenge high-energy electrons that would otherwise tend to degrade polyethylene chains, [ 24 ] and thus inhibit the formation of electrical trees, which is a major electrical breakdown mechanism of insulation materials. In particular, a high electron affi nity and a low ionization energy have been identifi ed as necessary criteria for effi cient electrical tree inhibition.…”
Section: Doi: 101002/adma201404306mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7] These additives scavenge high-energy electrons that would otherwise tend to degrade polyethylene chains, [ 24 ] and thus inhibit the formation of electrical trees, which is a major electrical breakdown mechanism of insulation materials. In particular, a high electron affi nity and a low ionization energy have been identifi ed as necessary criteria for effi cient electrical tree inhibition.…”
Section: Doi: 101002/adma201404306mentioning
confidence: 99%
“…Here, we demonstrate for the fi rst time that fullerenes can act as effi cient voltage stabilizers for polyethylene, i.e., additives that increase the dielectric strength of an insulation material. The development of such additives currently receives increasing attention because of their potential use in power cable insulation, [1][2][3][4][5][6][7] which may considerably enhance the transmission effi ciency of tomorrow's power grids. We establish this sought-after property for fullerenes by employing a suite of structural and electrical characterization techniques and fi nd that, on a molal basis, fullerenes are the most effi cient voltage stabilizers that have been identifi ed to date.…”
Section: Doi: 101002/adma201404306mentioning
confidence: 99%
“…It was found that the aromatic ring side groups are indispensable groups for suppressing electrical tree [9]. It was also found that aromatic ketones and diketones had great effects on inhibiting electrical treeing growth in XLPE and polyethylene (PE) [5,10]. Although much research has been carried out on the suppression effect of polycyclic compounds on electrical tree growth, the relationship between polycyclic compounds, charges, trapping levels, and electrical treeing is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that some organic polycyclic aromatic compounds or those with benzophenone-like structures, which serve as voltage stabilizers, can increase the resistance to electrical treeing effectively. [9][10][11][12][13][14][15] Using theoretical studies, our group rst elucidated the mechanisms of aromatic carbonyl compounds as voltage stabilizers for increasing the electrical breakdown strength of XLPE in 2013. [16][17][18] Acetophenone is an example of an aromatic carbonyl compound that can function as a voltage stabilizer; however, it easily migrates out of the polymeric matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, aromatic carbonyl and benzil-type compounds with a larger alkoxy chain can effectively increase the compatibility with the polyethylene matrix and improve the electrical treeing inception level signicantly. 13,14 This inspired us to investigate if polyethylene chains can be graed with voltage stabilizer molecules to yield stationary products during the UV radiation cross-linking process for the fabrication of XLPE insulation materials possessing permanent insulation performances.…”
Section: Introductionmentioning
confidence: 99%